Revitalizing Graduate Medical Education in Global Settings: Lessons From Post-Earthquake Haiti. (24th November 2020) - Morse, Michelle; Spahn, Lauren; Pierre, Paul; Lucien, Franciscka; Israel, Kerling; Toussaint, Sterman; Robert, Merly; Katz, Joel T.; Buyske, Jo; Clisbee, Mary; Suffrin, Dimitri J.C.; Raymonville, Maxi; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Following the massive 7.0-magnitude earthquake that devastated much of the Haitian capital city of Port-au-Prince on January 12, 2010, the Haitian health system and its medical education programs were fragmented, fragile, and facing a significant, overwhelming demand for clinical care. In response, the authors of this paper and the institutions they represent supported the development of a teaching hospital that could fill the void in academic training capacity while prioritizing the health of Haiti's rural poor—goals aligned with the Haitian Ministry of Health (MOH) strategy. This bold initiative aimed to address both the immediate and long-term health care needs within post-disaster Haiti through a strategic investment in graduate medical education (GME). Here, the authors describe their approach, which included building consensus, aspiring to international standards, and investing in shared governance structures under Haitian leadership. The Haitian MOH strategy and priorities guided the development, implementation, and expansion of solutions to the ongoing crisis in human resources for health within the acute context. Local leadership of this initiative ensured a sustained and transformative model of GME that has carried Haiti beyond acute relief and toward a more reliable health system. The enduring success can be measured through sustained governance systems, graduates who have remained in Haiti, standardized curricula, a culture of continuous improvement, and the historic achievement of international accreditation. While ongoing challenges persist, Haiti has demonstrated that the strategy of investing in GME in response to acute disasters should be considered in other global settings to support the revitalization of tenuous health systems.